Real Time Garbage Bin Capacity Monitoring - Nyayu Husni Latifah; Sitangsu Sitangsu; Sabilal Rasyad; Ade Silvia Handayani (Universitas Sriwijaya, 2020)
This paper discusses about a garbage bin that can be monitored in real time. The information of the garbage capacity can be obtained in the application that is integrated in the mobile phone. The communication between the garbage bin and the mobile phone is intended to help the garbage collector and the user to monitor the capacity of the garbage in a garbage bin. When it has been overloaded, the collector can manage the garbage by moving the garbage to the other bigger garbage bin. (landfill). This garbage bin has been tested and it could run well. It could open and close its cover as soon as it detected or did not detect the objects. It could also send the information of the garbage capacity to the mobile phone immediately with delay only 0.45-0.47 s.